Analisis Penerapan Kompetensi Pedagogik di Sekolah Negeri dan Swasta - Ummi Nur Afinni Dwi Jayanti; Luhlu Zahara; Lulu Ilmanun; Siti Putri Aprilia (Universitas Muhammadiyah Enrekang, 2023)
This study aims to obtain information about the application of Indonesian language teacher's pedagogic competence in learning, including to determine the teacher's ability to plan lessons in the subjects taught. This research is a type of qualitative research that is descriptive in nature. The data collection technique used in general is using interview techniques. Interviews were conducted by researchers with the reason that researchers were able to ask questions face to face with the participants. The results of the data analysis show that the application of pedagogic competencies in public and private schools is going well. This is because the Indonesian teacher prepares lessons regularly and uses several methods to make learning better. Indonesian language teachers in their own country improve the language skills of educators so that they are able to convey well to students and then make students understand and enjoy during the learning process which makes students like what is taught by educators.